Tindak Tutur Direktif Pada Kolom Komentar Tiktok @Ayah Amanah Terkait Video Ustaz Hanan Attaki Yang Di Unggah Pada 3 Mei 2025 - Yani, Tri Suci Handa; Ningsih, Rika (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2026)
This study aims to analyze directive speech acts in the TikTok comment section of @ayahamanah related to Ustaz Hanan Attaki's video "Be the best version of yourself" (May 3, 2025) with a focus on the functions of requesting, advising, recommending, asking, and requesting. The method used is qualitative with content analysis techniques, collecting data from the top 21 comments reflecting spiritual interactions on social media. The results show that the directive speech act of advising is the most dominant with 10 data (47.6%), followed by asking 4 data (19%), requesting and recommending 3 data each (14.3%), and requesting 1 data (4.8%). The dominance of speech acts of advising reflects the tendency of netizens to convey encouragement for self-change and spiritual motivation in the context of digital da'wah. This finding underscores that online religious communication prioritizes constructive speech acts as a means of strengthening community faith, with advice functioning as an invitation to istiqamah and asking as spiritual clarification. This study contributes to the understanding of Islamic communication patterns on TikTok that are harmonious and persuasive.